Nostos and Nineteenth-Century Italian-Canadian Immigration: Mapping the Earliest Latin Quarters - Cauchi-Santoro, Roberta (Italian Canadiana)

(untitled) (Iter Press, 2021)
In this article, I examine the formation of the first Latin Quarter in London (ON) at the end of the nineteenth century, and thus at the dawn of modernity. I analyse how these first (mostly Southern) Italian immigrants attempted to soothe their need for a sense of belonging, how they negotiated their collective nostos and, concomitantly, how they dealt with the palpable nostalgia for a return to their Mediterranean homeland.